Relationships of life satisfaction with commuting and built environment: A longitudinal analysis. (January 2023) - Wang, Xiaoquan; Wang, Weifeng; Yin, Chaoying; Shao, Chunfu; Luo, Sida; Liu, Erjian
Abstract: Although detrimental effects of commuting have been widely researched, little longitudinal evidence can be found regarding whether changes in commuting time and modes cause changes in life satisfaction. This study examines the relationships of life satisfaction with commuting from a longitudinal perspective. The effects of built environment are also examined. Using longitudinal survey data from 4505 respondents in China, the findings show that the increase in commuting time associates with losses in life satisfaction. Switching from non-active modes to active modes associates with increases in life satisfaction. Nonetheless, switching from active modes to non-active modes only reduces life satisfaction for people who experienced changes in some specific built environment attributes (e.g., increasing population density). Most changes in built environment associate with life satisfaction changes. The findings suggest that policy and planning efforts to promote active commuting and reduce commuting time (e.g., providing walkable and cyclist-friendly environment and promoting job–housing balance) should continue.